Komunikasi AntarBudaya Masyarakat Multikultur di Kelurahan Tangkiling Kecamatan Bukit Batu Kota Palangka Raya - Ni Nyoman Rahmawati (Dharma Duta, 2020)
This article aims to analyze and describe the articulation and forms of communication carried out by communities of different customs, cultures and religions in Tangkiling Village, Bukit Batu District, Palangkaraya City. The problem is studied using intercultural communication theory. The method used is descriptive qualitative method, in which the data obtained is presented in the form of words which are assembled from information obtained from informants in the field. The data were collected through observation, in-depth interviews, and document study. Informants are selected by purposive sampling by looking at the knowledge and experience they have according to the data to be sought. Then the data is processed through three stages, namely data collection, data reduction, and data presentation. The results showed that the harmony of the multicultural society in Tangkiling Village was seen from the activities carried out in their daily social interactions such as: religious tolerance, mutual respect cooperation, while the articulation of the Tangkiling community towards differences in cultural customs was seeing culture as just another person's way of doing things and culture it is only a habit that has been carried out from generation to generation which is formed from the geographical conditions of the area.The form of intercultural communication carried out by multicultural communities in Tangkiling Village is through cultural adaptations such as language adaptation, food adaptation, and adaptation in cultivating agricultural land.